1971
DOI: 10.2307/1934585
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide Effects on Early Succession in an Old Field Ecosystem

Abstract: An ecosystem approach was used to assess the effects of soil contamination with an organophosphate insecticide on ecological succession in 3—acre old field on the Piedmont of New Jersey. Diazinon was applied to one—half of the field in May 1967 and again in May 1967 and again in May 1968 at a rate of 12 lbs of active ingredient per acre. A latin square experimental design was used to analyze the effects of the insecticide on the density, diversity, and production of vegetation; the density and diversity of her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1974
1974
2008
2008

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…A common critique of using chemical suppression on insects is that effects on non‐target organisms can lead to incorrect interpretations (Wall & Reichman, 2000). Organisms other than insects were affected by some insecticides in this analysis (Shure, 1971; Clements et al ., 1982). All papers were recorded whose authors reported effects on earthworms or nematodes, or used an insecticide for which such non‐target effects were found in another study, as this was the most common non‐target effect.…”
Section: Methodsmentioning
confidence: 97%
“…A common critique of using chemical suppression on insects is that effects on non‐target organisms can lead to incorrect interpretations (Wall & Reichman, 2000). Organisms other than insects were affected by some insecticides in this analysis (Shure, 1971; Clements et al ., 1982). All papers were recorded whose authors reported effects on earthworms or nematodes, or used an insecticide for which such non‐target effects were found in another study, as this was the most common non‐target effect.…”
Section: Methodsmentioning
confidence: 97%
“…Barrett (1968), Malone ( 1969) and Shure ( 1971) attacked the problem by attempting to disrupt upper trophic levels with toxic substances. Barrett (1968), Malone ( 1969) and Shure ( 1971) attacked the problem by attempting to disrupt upper trophic levels with toxic substances.…”
Section: Comparisons With Other Types Of Perturbationsmentioning
confidence: 99%
“…Interference with enzyme pathways may reduce seed germination and plant growth (Shure, 1971). Furthermore, these effects may be speciesspecific.…”
Section: Introductionmentioning
confidence: 99%